RENCANA STRATEGI PESANTREN SEBAGAI LEMBAGA PENDIDIKAN DI INDONESIA - Darliana Sormin (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2017)
Islam suffered a setback when confined with taklid and ignored science. When Islam leaves science and experiences stagnation, other nations and nations rise from adversity. Finally, now in some period of time Islam suffered. Therefore it is time for pesantren, madrassas and Islamic schools to lift the fall of the Indonesian people in particular and mankind in general today. The roles of madrassas and scholarship such as Baitul Hikmah in the glory of Islam, which has made significant contributions to the progress of Islam, can be transferred by pesantren, madrasah and Islamic schools to be applied today, so that these three Islamic institutions become science laboratories religious and scientific research activities center.Keywords: Strategic Plan, Pesantren, Educational Institution